Visualization of Cardiac Vectors using Electrocardiography and Magnetocardiography. Issue 1 (2nd January 2023) - Bhat, Vikas R.; Sengottuvel, S.; Swain, Pragyna P.; Anitha, H.; Gireesan, K.
Abstract : In this paper, an attempt is made to simulate and compare spatio-temporal VCG and VMCG derived from epicardial potentials. Electric (EHV) and Magnetic heart vectors (MHV) are computed from the ECG and MCG at various time instants and their orientations with respect to time are found to show a reasonable tilt of 90 to 100 degrees. The complimentary information with reference to the orientation of cardiac vector offered by MHV could be attributed to its sensitivity to intracellular myocardial currents, while EHV exhibits the orientation associated with only the extracellular currents owing to volume conduction. By comparing the orientations of EHV and MHV generated from a simulated equivalent current dipole model, the present work demonstrates the usefulness of these spatiotemporal vectors in tracing the cardiac current flow inside the thorax for a healthy heart. It could be thus expected that clinically relevant information could be obtained if the present analysis is extended to highly complex and irregular cardiac activation sequences that could be seen in arrhythmia and myocardial infarction. The main contribution of this paper is to mathematically model and derive the magnetic heart vectors from the MCG system extracted from IGCAR lab and verify it with the conventional VCG extraction..